Problems of ensuring media safety in the field of ethnic relations - Linar R. Zakirov, Vasil Z. Garifullin, Lyailya R. Sabirova, (Opción, 2019)
The article is devoted to the study of various aspects of media security, which is actually a prerequisite of the universal well-being of citizens. The authors used traditional empirical and general scientific methods, including historical, analysis and synthesis, observation, comparison. As a result, particular emphasis is placed on the mechanisms for creating and strengthening ethnic media security, which is aimed at regulating social relations based on the principles of multiculturalism and tolerance. In conclusion, media security becomes the national strategy of many states in the conditions of an accelerating globalization process.